Theory and Relevance of Currency Substitution with Case Studies for Canada and the Netherlands Antilles - de Vries, Casper G. (The Review of Economics and Statistics, 1988)
Casper G. de Vries, Theory and Relevance of Currency Substitution with Case Studies for Canada and the Netherlands Antilles, The Review of Economics and Statistics, Vol. 70, No. 3 (Aug., 1988), pp. 512-515